Narcos : México, représentation d’une réalité mexicaine ? - Nadia Tahir (Les Cahiers ALHIM)
For its three seasons, Narcos: México, is built on giving a significant place to various historical events in Mexico through a voice-over, the use of archival footage and the integration of Mexican political figures within the plot. These tools allow the production of the series to indicate that the drug traffickers, the majority of the protagonists, are not just fictional characters. Thus, these characters would not be stereotypes or convey stereotypes about Mexican reality since they are part of it. Narcos: México is an entertainment series, but it aims to depict a historical reality of Mexico. From then on, we can wonder about the contribution of the fiction-reconstruction mix to the understanding of events linked to drug trafficking, and the risk that it may feed stereotypes, or even anchor them a little more in a collective imagination by accompanying them with the seal of "truth". By analysing the various tools of the series in the service of historical reality, we wish to show that the production does not entirely escape this pitfall.